Scubatex resources diving into window of opportunities / Yasmin Kamall Khan, Azlin Shafinaz Arshad and Zanariah Zainal Abidin. - Kamall Khan, Yasmin; Arshad, Azlin Shafinaz; Zainal Abidin, Zanariah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
This case study is about Scubatex Resources, Malaysia SME, founded in 2007 as a new firm in Asia's scuba diving industry. Scubatex was founded by Mastura Abdul Manap, an engineer by profession but possessing a deep passion for diving. Mastura started the business as a distributor of scuba diving equipment with the help of her husband. Both Mastura and her husband have worked tirelessly for the first two years, growing the business by leaps and bound. She registered Scubatex Resources as a private limited company (Sdn Bhd) in 2009 to become an established and respected firm in Malaysia's scuba diving industry. Although the risks and challenges involved in investing in the scuba industry are significant, there is always the opportunity for the company to be more flexible and focus on niche markets. The company has far greater growth potential in the industry.